Evaluation of a rotating drum mixer - C R Stark; C H Fahrenholz; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1991)
A "rotating drum" type mixer was tested to determine if it could produce a uniformly mixed feed. Feed was manufactured in four separate trials, which examined addition sequence, mixing time, mixer capacity, and liquid addition. Uniformly mixed feed was obtained after 8 min, when ingredients were properly sequenced and mixed. Smaller batch sizes decreased the time required to obtain a uniform mixture. The mixer distributed liquid uniformly through the feed and had excellent clean-out capabilities.; Swine Day, Manhattan, KS, November 21, 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Rotating drum mixer; Feed uniformity; Feed manufacturing; Mixer testing